Ann Grodzins Gold. A Carnival of Parting: The Tales of King Bharthari and King Gopi Chand As Sung and Told by Madhu Natisar Nath of Ghatiyali, Rajasthan. Berkeley: University of California Press, 1992. - Lorenzen, David N. (Estudios de Asia y África, 1994)
John D. Smith. The Epic of Pabuji: A Study, Transcription and Translation, Cambridge, Cambridge University Press, 1991.